2021
DOI: 10.1177/00236772211016926
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary oral dosing for precise experimental compound delivery in adult rats

Abstract: Preclinical drug studies routinely administer experimental compounds to animal models with the goal of minimizing potential adverse events from the procedure. In this study, we assessed the ability to train adult male Long Evans rats to accept daily voluntarily syringe feedings of l-3,4-dihydroxyphenylalanine (L-DOPA) compared to intraperitoneal (IP) injections. Rats were trained to become familiar with the syringe and then fed a training solution that did not contain the experimental compound. If the rat was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the levodopa-treated group, rats were orally administered 10 mg/kg L-dopa between 15:00 and 16:00 once daily for 4 weeks, 7 days a week. Levopar tablets were freshly prepared daily before administration [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the levodopa-treated group, rats were orally administered 10 mg/kg L-dopa between 15:00 and 16:00 once daily for 4 weeks, 7 days a week. Levopar tablets were freshly prepared daily before administration [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…3 Chesler K C et al applied compound training to 22 youth football players. 4 The results showed that the implementation of compound training in youth football players not only compensated for the reduction in strength and explosiveness during the offseason, but some players even improved some sports performance. Burke A. in order to compare the effect of traditional compound training and new compound training on the explosive power of men's volleyball players, after 8 weeks of intervention, it was found that there was no significant difference between the three groups in the effect of the maximum bending moment of both knees.…”
Section: Introductionmentioning
confidence: 95%